ATTITUDE OF PHYSIOTHERAPISTS TOWARDS DISABLED PERSONS: http://doi.org/10.46536/jpumhs/2024/14.02.510 - Syeda Nayab Batool1, Muhammad Adnan Haider2, Maham Riaz3, Imtiaz Ali4, Munesh Kumar5, Sain Memon6, Alina Irshad7, Kiran Bibi8 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Attitude is a point of view of some one about unspecified thing. Attitude is a reflecting tool which presents our personality and response towards something or someone which based on knowledge and experience or the personal thoughts. OBJECTIVE: The objective of this study is to assess the response of physiotherapist towards disabled person. METHODS: A Cross sectional study was conducted over two thirty eight participants. Non probability purposive sampling technique was used. And data was collected form physiotherapists (students and professionals) of different private and government sector. Overall response of physiotherapists was obtained. SPSS version 21 was used for data analysis. Attitude towards disabled person (ATDP Form O) scale was used to assess the attitude towards disabled person. Attitude towards disabled person scale (ATDP Form O) is used for one-dimensional attitude and consists of 20 item scale. RESULTS: Out of total 238 participants 216 (90.4%) were those who showed positive attitude towards disabled person and 22 (9.2%) were those who showed negative attitude. In this study overall a very positive response of physiotherapists was obtained towards disabled person. CONCLUSION: In this study positive response was obtained by physiotherapists towards disabled person who showed the professional attitude of physiotherapists towards their patients. And further investigation is required to assess what disabled person thought about physiotherapist’s response towards them.